2019
DOI: 10.3390/cancers11071011
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Basis of Melatonin Protective Effects on Breast Cells Treated with Doxorubicin: TWIST1 a Transcription Factor Involved in EMT and Metastasis, a Novel Target of Melatonin

Abstract: Melatonin mitigates cancer initiation, progression and metastasis through inhibition of both the synthesis of estrogens and the transcriptional activity of the estradiol-ER (Estrogen receptor) complex in the estrogen-dependent breast cancer cell line MCF-7. Moreover, melatonin improves the sensitivity of MCF-7 to chemotherapeutic agents and protects against their side effects. It has been described that melatonin potentiates the anti-proliferative effects of doxorubicin; however, the molecular changes involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 95 publications
1
35
0
Order By: Relevance
“…We initially performed a systematic meta-analysis to identify miRNA expression profiles targeted by melatonin in experimentally relevant studies. Based on the design criteria for eligibility ( Figure 1), 14 studies [47][48][49][50][51][52][53][54][55][56][57][58][59][60] were selected to investigate the miRNAs expression changes induced by melatonin treatment (Table S1). Among the 46 differentially expressed miRNAs, 29 were upregulated, and 17 were downregulated (Table S2).…”
Section: The Meta-analysis Identified 46 Mirnas Differentially Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially performed a systematic meta-analysis to identify miRNA expression profiles targeted by melatonin in experimentally relevant studies. Based on the design criteria for eligibility ( Figure 1), 14 studies [47][48][49][50][51][52][53][54][55][56][57][58][59][60] were selected to investigate the miRNAs expression changes induced by melatonin treatment (Table S1). Among the 46 differentially expressed miRNAs, 29 were upregulated, and 17 were downregulated (Table S2).…”
Section: The Meta-analysis Identified 46 Mirnas Differentially Exprmentioning
confidence: 99%
“…[51][52][53][54] The upregulation of miR-10a, miR-10b, and miR-34a by melatonin is likely due to the inhibition of the TF TWIST1, which plays a role in EMT, metastasis, and angiogenesis in estrogen-dependent breast cancer cells. 54 Upregulated miRNAs by melatonin are linked to inhibition of drug resistance and apoptosis induction, but not autophagy in oral carcinoma cells; these effects are mediated by AKT, c-Jun N-terminal kinase (JNK), and p38. 55 We further document the enhancement of biological processes and protein binding based on our interactome analysis.…”
Section: Of 19mentioning
confidence: 99%
“…cell-signaling pathways that are key for the proliferation and survival of BC cells, as well as for metastasis and resistance to anti-cancer drugs [217,224,225]. Otherwise, traditional oncology has clearly shown that antiestrogens are an effective measure in the treatment of ER+ BC, using either Tamoxifen or Letrozole.…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%
“…ERs can be activated when cells are exposed to estrogen. [7][8][9] Emerging evidence shows that the activation of ERs is highly associated with cancer formation and metastasis, [10][11][12] extracellular matrix (ECM) remodeling 2,13 and drug resistance. [14][15][16][17] Here, we focus on providing a comprehensive understanding of ERα.…”
Section: Introductionmentioning
confidence: 99%